Evaluating a new approach to learning design - Conole, Gráinne; Mundin, Paul; Galley, Rebecca (Proceedings of the International Conference on Networked Learning, 2012)
Technologies, and in particular social and participatory media, provide rich opportunities to support a range of pedagogies and enable learners to communicate and collaborate with their peers. However, despite this technologies are not being used extensively. A new research theme, learning design, has emerged in recent years, which aims to address this gap between the potential and actual use of technologies. This paper argues that designing for learning is the key challenge faces education today. Practitioners need guidance on how to make informed design decisions about how to harness the characteristics of new technologies. Learning design tools and resource have been created that can both guide practitioners through the design process and enable them to make their designs explicit so that they can be shared and discussed. Learning design as a term has being used in a number of different ways, for the purposes of this paper it is defined as follows: A methodology for enabling teachers/designers to make more informed decisions in how they go about designing learning activities and interventions, which is pedagogically informed and makes effective use of appropriate resources and technologies. This includes the design of resources and individual learning activities right up to curriculum-level design. A key principle is to help make the design process more explicit and shareable. Learning design as an area of research and development includes both gathering empirical evidence to understand the design process, as well as the development of a range of resource, tools and activities. Learning design is distinct from, but related to other research areas, such as: instructional design, pedagogical patterns and Open Educational Resources (OER). The paper draws in particular on the development of a learning design methodology as part of the OU’s learning design initiative. The paper will describe the evaluation of this new learning design methodology as part of an EU-funded project, Design Project. The methodology will be described, along with the learning design resources, tools and activities that have been developed. The methodology has been trialled in the UK, Cyprus and Greece and the paper will report on the evaluation of a series of trials carried out in the UK.